Pengaruh Warisan Budaya Gedung Sate Terhadap Identitas Kota Bandung - Hazib; Suminar, Imas Ratna; Hasanah, Isti Marwah; Maulana, Permana Bayu; Hermanto, Odang (Journal of Contemporary Issues in Primary Education, 2024)
Gedung Sate is a very important cultural and historical icon for the city of Bandung, with unique architecture and full of symbolic meaning. This research aims to identify the influence of Gedung Sate as a cultural heritage on the formation of the identity of the City of Bandung. To achieve this goal, the research used qualitative methods with literature analysis and field observations. Literature analysis was carried out by reviewing various written sources that discuss the history, architecture and role of Gedung Sate in the development of the city, while field observations were carried out to observe the relationship between this building and the lives of the people around it. The results of the research show that Gedung Sate does not only function as an administrative symbol West Java, but has also become an integral part of the collective identity of the people of Bandung. Gedung Sate strengthens the city's image as a tourist destination rich in history and culture. Its existence, which is closely connected to the social and cultural life of the community, makes this building a symbol of pride that connects the past with the present. Thus, Gedung Sate plays a major role in shaping the identity of the city of Bandung and improving the city's image in the eyes of the world.